2014
DOI: 10.3109/08039488.2014.981856
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma in the lives of substance-dependent patients: The relationship between depression, anxiety and self-esteem

Abstract: This study showed high levels of childhood traumatic experiences for SD people and indicates that there may be a relationship between these experiences and their levels of self-esteem, depression and anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…Several studies have documented the association between adverse childhood events and adult substance abuse (Ekinci and Kandemir, 2014). Specifically, childhood sexual abuse (Cuellar and Curry, 2007; Vera et al, 2005) physical abuse and neglect (Mersky et al, 2013) have been identified as important risk factors for the development of substance abuse in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented the association between adverse childhood events and adult substance abuse (Ekinci and Kandemir, 2014). Specifically, childhood sexual abuse (Cuellar and Curry, 2007; Vera et al, 2005) physical abuse and neglect (Mersky et al, 2013) have been identified as important risk factors for the development of substance abuse in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…CSA is linked to other syndemic pathways including depression, substance use, and post-traumatic stress disorder (PTSD), which may develop even years later and are linked synergistically to perpetuate risk behavior (Parsons et al, 2011; Rowan & Foy, 1993; Rowan et al, 1994; Stall et al, 2003). Both CSA and PTSD are associated with a host of comorbid psychological health issues in adulthood, including substance use disorders (Banducci et al, 2014a; Suvak et al, 2012), low self-esteem (Browne & Finkelhor, 1986; Ekinci & Kandemir, 2015; Payne et al, 2014), and difficulty regulating emotions including distress intolerance (Stevens et al, 2013). CSA and related psychological and health sequelae, have also been associated with HIV-related condomless sex (Banducci et al, 2014a, b; Boroughs et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that posttraumatic symptoms are related to self-esteem. Self-esteem is of critical importance when considering adaptive functioning in the face of adversity, as it has been linked to traumatic experiences (e.g., Ekinci & Kandemir, 2015), recidivism (Cook, 2014), substance abuse (e.g., Stein et al, 2002), and other maladaptive outcomes (e.g., suicidality; Eskin, 2012). Focusing trauma-informed efforts on those displaying posttraumatic stress symptoms and focusing those efforts on symptom reduction will optimize treatment in promoting adaptive functioning and thus improve perceptions of self-worth and self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence to suggest that an individual’s self-esteem, self-concept, and self-worth are shaped by having experienced a trauma and/or having posttraumatic stress symptoms (e.g., Ekinci & Kandemir, 2015). Childhood maltreatment and family violence have been associated with lower self-esteem in adulthood (Liem & Boudewyn, 1999), and Soler, Paretilla, Kirchner, and Forns (2012) found lower levels of self-liking in those who had experienced multiple victimizations compared to those with one victimization experience.…”
mentioning
confidence: 99%